Promoting the health and well-being of English-speaking Seniors in Quebec. A community model (infographic) - Community Health And Social Services Network/Réseau communautaire de santé et de services sociaux (2019)
fs-ref-orig: Community Health And Social Services Network. (2019). Promoting the health and well-being of English-speaking Seniors in Quebec. A community model [infographic]. fs-code-orig: Community Health And Social Services Network-2019

Identifying second language speech tasks and ability levels for successful nurse oral interaction with patients in a linguistic minority setting: An instrument development project - Isaacs, Talia; Laurier, Michel. D.; Turner, Carolyn. E.; Segalowitz, Norman (Health communication, 2011)
One of the most demanding situations for members of linguistic minorities is a conversation between a health professional and a patient, a situation that frequently arises for linguistic minority groups in North America, Europe, and elsewhere. The present study reports on the construction of an oral interaction scale for nurses serving linguistic minorities in their second language (L2). A mixed methods approach was used to identify and validate a set of speech activities relating to nurse interactions with patients and to derive the L2 ability required to carry out those tasks. The research included an extensive literature review, the development of an initial list of speech tasks, and validation of this list with a nurse focus group. The retained speech tasks were then developed into a questionnaire and administered to 133 Quebec nurses who assessed each speech task for difficulty in an L2 context. Results were submitted to Rasch analysis and calibrated with reference to the Canadian Language Benchmarks, and the constructs underlying the speech tasks were identified through exploratory and confirmatory factor analyses. Results showed that speech tasks dealing with emotional aspects of caregiving and conveying health-specific information were reported as being the most demanding in terms of L2 ability, and the most strongly associated with L2 ability required for nurse–patient interactions. Implications are discussed with respect to the development and use of assessment instruments to facilitate L2 workplace training for health care professionals.

Promoting the health and well-being of English-speaking seniors in Quebec. A community model - Kueber, Rusell (Community Health and Social Services Network, 2019)

Promotion de la santé et du bien-être des aînés d’expression anglaise du Québec : un modèle communautaire - Kueber, Russell (Réseau communautaire de santé et de services sociaux, 2019)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire( infographie) - Réseau communautaire de santé et de services sociaux/Community Health and Social Services Network (2019)
fs-ref-orig: Réseau communautaire de santé et de services sociaux. (2019). Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire [infographie]. fs-code-orig: Réseau communautaire de santé et de services sociaux-2019

Améliorer la santé et le bien être des Madelinots anglophones. Une stratégie pour un développement sain des jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Anglophone Magdalen Islanders, 2018)
fs-ref-orig: Richardson, M. et Ledoux, J.-J. (2018). Améliorer la santé et le bien être des Madelinots anglophones. Une stratégie pour un développement sain des jeunes. Council for Anglophone Magdalen Islanders. fs-code-orig: Richardson-2018

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.